Perioperative and mid-term prognosis in coronary artery bypass grafting patients with mild renal dysfunction - Wuwei Wang; Xu Cao; Yukai Wu; Quan Liu; Yifei Zhou; Rui Fan; Xin Chen; Rui Wang (Renal Failure)
Objective Renal dysfunction is the most common risk factor for patients with coronary artery bypass grafting (CABG). The aim of this research was to evaluate the prognosis and mid-term outcomes in CABG patients with mild renal dysfunction.Methods Patients undergoing isolated CABG from July 2020 to December 2022 in Nanjing First Hospital were selected into this cohort study and divided into normal renal function group (eGFR ≥ 90 mL/min/1.73 m2, corresponding to CKD G1) and mild renal dysfunction group (eGFR: 60–89 mL/min/1.73 m2, corresponding to CKD G2). Propensity score matching was used to balance the differences. The primary outcomes were acute kidney injury (AKI) and all-cause mortality in follow-up, while the secondary outcomes were perioperative mortality and major adverse cardiac and cerebrovascular event (MACCE) including death, stroke, myocardial infarction, and revascularization.Results Totally 1,097 patients were enrolled in this study and 416 (33.3%) had mild renal dysfunction. A total of 379 pairs were included to the analysis after propensity score matching. Compared with the normal renal function, patients with mild renal dysfunction had more AKI after CABG (26.1% vs. 18.7%, p = 0.015), however, the perioperative mortality (1.3% vs. 1.3%, p = 1.00) was not significantly different. At 3-year follow-up, there were also no significant differences in all-cause mortality (6.3% vs. 4.8%, log-rank p = 0.33, HR 1.38, 95%CI: 0.721–2.652) and MACCE rates (10.2% vs. 7.6%, log-rank p = 0.19, HR 1.42, 95%CI: 0.836–2.414).Conclusion For patients undergoing CABG, preoperative renal dysfunction is associated with an increased risk of postoperative AKI. However, no significant difference was observed in perioperative mortality and mid-term outcomes.